Rapid vibrational imaging with sum frequency generation microscopy - Raghunathan, Varun (2011)
We demonstrate rapid vibrational imaging based on sum frequency generation (SFG) microscopy with a collinear excitation geometry. Using the tunable picosecond pulses from a high-repetition-rate optical parametric oscillator, vibrationally selective imaging of collagen fibers is achieved with submicrometer lateral resolution. We furthermore show simultaneous SFG and second harmonic generation imaging to emphasize the compatibility of the microscope with other nonlinear optical modalities.